Академічна прокрастинація в іноземних студентів бакалаврату в умовах лінгвокультурної інтеграції - Журавльова, Олена; Засєкіна, Лариса; Журавльов, Олександр; Zhuravliova, Olena; Zasiekina, Larysa; Zhuravliov, Oleksandr (Lesya Ukrainka Eastern European National University, 2019)
The article is focused on revealing the factors of acculturation and language adaptation through the study of the specific character of procrastination in international students. The specific features of the operationalization of these concepts in modern psychological literature. The peculiarities of the operationalization of these concepts in modern scientific literature are highlighted. Among the research participants were international undergraduate students (n = 41) who study at two higher education institutions of Ukraine. Results of the correlation analysis indicate a positive correlation between procrastination with the general level of acculturation stress (r=0.43, p <0.01), as well as its aspects as an acculturation fear (r= 0.46, p <0.01), discriminated perception (r=0.37, p <0.05), feeling of guilt (r=0.31, p <0.05). Great significance of the aspects of language integration in the context of studying the subject of procrastination is confirmed by stable direct correlations with the general scale of speech anxiety (r = 0.59, p <0.001), fear of negative evaluation (r = 0.62, p <0.001), fear of communication (r = 0.62, p <0.001), and exams (r = 0.47, p <0.01).У статті обґрунтовано актуальність вивчення чинників акультурації та мовної адаптації у контексті дослідження специфіки прояву прокрастинації іноземними студентами. Висвітлено особливості операціоналізації вказаних понять у сучасній науковій літературі. Вибірку дослідження склали іноземні студенти (n=41), які навчаються за освітнім рівнем «бакалавр» у двох вищих навчальних закладах України. Результати кореляційного аналізу свідчать про позитивний взаємозв’язок прокрастинації із загальним рівнем прояву стресу акультурації (r = 0.43, p<0,01), а також такими його аспектами як акультураційний страх (r = 0.46, p<0,01), сприйнята дискримінація (r = 0.37, p<0,05), почуття провини (r = 0.31, p<0,05). Вагоме значення аспектів мовної інтеграції у контексті вивчення тематики прокрастинації підтверджено зафіксованими прямими значущими кореляційними зв’язками із загальною шкалою мовної тривожності (r = 0.59, p<0,001), страхом негативної оцінки (r =
Academic Procrastination Among International Undergraduate Students Under the Conditions of Linguistic and Cultural Integration
Keywords: прокрастинація; акультураційний стрес; мовна адаптація; мовна тривожність; іноземні студенти; procrastination; acculturation stress; language adaptation; language anxiety; foreign students